Metabolic reconstituent or monosodium glutamate response on pregnancy rate in ewes: Tasa de gestación en ovejas con dos fuentes de aminoácidos - Hernández Marín, José Antonio; Ángel-Sahagún, César Andrés; Rojas-García, Adelaido Rafael; Cigarroa-Vázquez, Francisco Antonio; Maki-Díaz, Griselda; Cadena-Villegas, Said (Ecosistemas y Recursos Agropecuarios, 2025)
The action of a metabolic restorative (REC) and monosodium glutamate (GLU) was evaluated during the synchronization of estrus in ewes, with progestogen (CIDR) and prostaglandins (PGF2α). Fifty-four multiparous ewes were used and randomly assigned to one of three treatments: CONTROL (n = 18): 50 mL of saline subcutaneously (SC) and 50 mL of saline orally (PO); REC (n = 18): 50 mL of a metabolic restorative via SC and 50 mL of saline PO; GLU (n = 18): 0.5 g of monosodium glutamate per kg of live weight, dissolved in 50 mL of physiological saline PO and additionally, 50 mL of physiological saline via SC. REC and GLU were administered once daily for the last three days prior to CIDR withdrawal. For the analysis of the variables expressed in %: response to estrus (RE), duration of estrus (DE), return to estrus (RET) and pregnancy (GES), the c2 test was used and the data on the onset of estrus (OE) and duration of estrus (DE) were analyzed with the Kruskal-Wallis test. The response was different (P ≤ 0.05) for RE, DE and GEST, but similar (P > 0.05) for OE and RET in ewes were synchronized with CIDR and PGF2α. Monosodium glutamate improves the response to estrus, the duration of estrus and the pregnancy rate, without affecting the onset of estrus or the return to estrus in ewes synchronized with a progestogen and prostaglandins.